2021
DOI: 10.3390/su132313177
|View full text |Cite
|
Sign up to set email alerts
|

Current Readiness Status of Electric Vehicles in Indonesia: Multistakeholder Perceptions

Abstract: As a net oil importer since 2004, Indonesia’s success in developing fuel economy and infrastructure for electric vehicles would be vital to ensuring energy security and decarbonization from the transport sector. Following the Presidential Regulation on the Acceleration Program for battery-based EV for Road Transportation in 2019, the Indonesian government provides incentives for the domestic production of EVs. However, as EV technology is relatively new for the domestic automotive industry in Indonesia, it nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 88 publications
0
33
0
Order By: Relevance
“…55 of 2019 on the Acceleration Program of Battery Electric Vehicles for Road Transport was published in 2019 to establish a legal umbrella for electric vehicle development in Indonesia. This regulation enabled several ministries to initiate electric vehicle projects in the country [47].…”
Section: Policies For Ev Sales and Usage In The Worldmentioning
confidence: 99%
“…55 of 2019 on the Acceleration Program of Battery Electric Vehicles for Road Transport was published in 2019 to establish a legal umbrella for electric vehicle development in Indonesia. This regulation enabled several ministries to initiate electric vehicle projects in the country [47].…”
Section: Policies For Ev Sales and Usage In The Worldmentioning
confidence: 99%
“…To help accelerate the transition to electric vehicles in Indonesia, President Joko Widodo issued Presidential Regulation No. 55 of 2019 in the form of incentives to assist the transition from internal combustion engines to an electric vehicle (Maghfiroh et al, 2021). However, there was only 0.15 percent of EVs on the road at the end of September 2020 (IESR, 2021).…”
Section: Overview Of Electric Vehicle Industry In Indonesiamentioning
confidence: 99%
“…Numerous studies have identified consumer range anxiety as one of the significant barriers to the adoption of electric vehicles (Liao et al, 2017;Maghfiroh et al, 2021;Marciano & Christian, 2020). This is undoubtedly true when the drivers notice power depletion while driving are unsure how far they can travel on their remaining battery charge, or when trips are suddenly extended (Graham-Rowe et al, 2012).…”
Section: Range Anxietymentioning
confidence: 99%
“…Indonesia can seize this opportunity because Indonesia is a producer of one of the battery components, namely nickel which covers 29.8% of world production [12]. Through Presidential Regulation Number 55 of 2019 regarding the acceleration of the electric vehicle battery industry development program, Indonesia has become a legal umbrella for building renewable energy challenges in line with the Paris Agreement goals [13]. However, Indonesia faces the challenge of a lawsuit from the European Union to the WTO in the development of the electric vehicle battery industry.…”
Section: Introductionmentioning
confidence: 99%